Dynamic Computed Tomography of the Brain: Techniques, Data Analysis, and Applications - Norman, David; Axel, Leon; Berninger, Walter H.; Edwards, Michael S.; Cann, Christopher E.; Redington, Rowland W.; Cox, Lauranne (American Journal of Neuroradiology, 1981)
Rapid sequence computed tomography (CT) scanning has many potential applications in studying intracranial physiologic events. However, visual inspection of these rapid sequence scans fails to extract the large amount of information inherent in the digital data. The concept of corrected mean transit time applied to rapid sequence scans after intravenous bolus injection of contrast material provides quantitative data on relative hemispheric flow. Use of histogram-based areas of interest permits accurate and reproducible identification of anatomic structures including arteries and gray and white matter. Gamma variate curve fit techniques reduce statistical noise. The concept of transit time can be expanded to the creation of functional CT images.